Determination of the Minimum Time of the Permission Signal of Traffic Lights at Intersections - Razzoqov Mashrab Ro’zievich; Ikromov Akmaljon G’ofurjonovich (Zien Journals, 2022)
This article presents a number of reasons for the traffic capacity of the intersection at the moment, which is based on the behavior of the vehicle when passing through the intersection and the time interval required to turn on the traffic light.
Keywords: traffic intensity; traffic light cycle; intersection; driver